Clinical Management of the Microbiome in Irritable Bowel Syndrome - Andrews, Christopher N (J Can Assoc Gastroenterol, 2020)
BACKGROUND: A growing body of evidence suggests that dysbiosis contributes to the onset and symptomatology of irritable bowel syndrome (IBS) and other functional bowel disorders. Changes to the gastrointestinal microbiome may contribute to the underlying pathophysiology of IBS. METHODS: The present review summarizes the potential effects of microbiome changes on GI transit, intestinal barrier function, immune dysregulation and inflammation, gut–brain interactions and neuropsychiatric function. RESULTS: A multimodal approach to IBS management is recommended in accordance with current Canadian guidelines. Pharmacologic treatments are advised to target the presumed underlying pathophysiological mechanism, such as dysregulation of GI transit, peristalsis, intestinal barrier function and pain signalling. The management plan for IBS may also include treatments directed at dysbiosis, including dietary modification and use of probiotics, which may promote the growth of beneficial bacteria, affect intestinal gas production and modulate the immune response; and the administration of periodic short courses of a nonsystemic antibiotic such as rifaximin, which may re-establish microbiota diversity and improve IBS symptoms. CONCLUSION: Dysregulated host–microbiome interactions are complex and the use of microbiome-directed therapies will necessarily be empiric in individual patients. A management algorithm comprising microbiome- and nonmicrobiome-directed therapies is proposed.